Power flow control in the converters interconnecting AC-DC meshed systems - Jardini, Jose Antonio; Sousa, Thales; Romero, Rubén A.; Rider, Marcos J.; Horita, Marco Antonio Barbosa; Bassini, Marcos; Cavalheiro, Marcos Rodolfo (My University, 2015)
DC grids are being strongly considered as a technology to be used for future expansions of the transmission system. Voltage sourced converters (VSC) are the key equipment considered for AC/DC interconnections. However the flow from DC to AC system has to be properly set as many alternatives exists. In this article, an Optimal Power Flow (OPF) to control the flow of power in the converters interconnecting AC-DC systems is presented. The proposed OPF solution technique was tested using the CIGRE B4 DC Grid Test System.
Power Flow Control in the Converters Interconnecting AC-DC Meshed Systems
Keywords: AC-DC Grid; Optimal Power Plow; Power Flow Control; VSC Converters